Efektivitas Pemanfaatan Media Video Pembelajaran bagi Siswa Fase E Pada Mata Pelajara Informatika di SMAN 1 Matur - Wulandari, Lusi; Syafril, Syafril; Hendri, Nofri; Rahmayanti, Elsa; Amsal, Mutiara Felicita (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The learning process carried out by teachers does not utilize media that is in accordance with informatics materials, resulting in a lack of enthusiasm and interest for students. This study aims to determine the effectiveness of the use of learning video media for phase E students in the Informatics subject at SMAN 1 Matur. The type of research used is a quantitative approach with a quasi-experimental method. The research design used is a Nonequivalent Control Group with a design form that provides different treatment to each class. The sampling technique used in this study is purposive sampling. The data needed was obtained from the students' learning outcomes, written and practical tests. The data obtained were analyzed using a t-test which was previously carried out first a normality test and a homogeneity test